eLingua : Issue 2 : JULY 2016 / Academy of Language Studies - Mohd. Amin, Noraziah; Aboo Bakar, Rofiza; Ab. Rahim, Suzana; Razali, Wan Noorli; Chone, Liaw Shun; Ismail, Rushita; Yih, Mah Boon; Giap, Lim Soo; Ahmad Zubir, Hanani (Academy of Language Studies, 2016)
1. The New Campus Rector’s Meeting with ALS Staff 2. Copy Right and Intellectual Property Workshop: How to Protect Your Work? 3. Mari Pelajari Bahasa Thai 4. EDMODO Workshop 2016 5. iLearn Workshop for APB 6. Northern Region Vetting Programme for ELC & EWC Codes 7. APB Academic Tour 2016 8. A Report on the English Exit Test (EET699) Briefing 9. Glory at KIK 2016!!! 10. Education Leadership Award to Dr. Mah Boon Yih!!! 11. Language through songs … (10 March 2016) 12. Aerobics in English … (12 May 2016) 13. The sound of music … (12 May 2016) 14. Poets, News Readers, Actors … (21 July 2016) 15. EdTech Seminar 2016 on WeCWI: The Instructional and Technological Discoveries 16. Innovate Teaching toward Personalised Learning through WeCWI Integrated Solutions 17. Seminar on WeCWI Enterprise: Write It Right 18. WeCWI: Redefine WBI as an LMS's Alternative for Higher Education 19. Mempelajari Simpulan Bahasa Mandarin: Kāitiānpìdì 20. BRONZE MEDALLION: THE URGE OF CONTINUING A LEGACY